2013
DOI: 10.1186/1477-7819-11-84
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of ulinastatin on postoperative complications, immunosuppression, and recurrence in esophagectomy patients

Abstract: BackgroundTo evaluate the potential efficacy of preventive effect of ulinastatin in esophagectomy patients.MethodsEighty patients with esophageal cancer were preoperatively allocated at random into two equal groups. Ulinastatin was administered to the treatment group (U) whereas the control group (C) received a placebo. The arterial oxygen tension and carbon dioxide tension were measured and the respiratory index (RI) was calculated. Plasma levels of circulating T lymphocyte subsets and interleukin 6 (IL-6) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…However, additional randomized controlled trials should be done to evaluate this strategy 77. Ulinastatin prevents postoperative complications and immunosuppression in esophagectomy patients, thereby prolonging RFS 78. Yamana et al 79.…”
Section: Resultsmentioning
confidence: 99%
“…However, additional randomized controlled trials should be done to evaluate this strategy 77. Ulinastatin prevents postoperative complications and immunosuppression in esophagectomy patients, thereby prolonging RFS 78. Yamana et al 79.…”
Section: Resultsmentioning
confidence: 99%
“…Whether inhibition of overproduction of inflammatory cytokines or neutrophil elastase is meaningful to reduce complications is still an ongoing issue. 23,24 We conclude that development of postoperative complications is an independent disease-specific poor prognostic factor after curative resection for patients with less-advanced esophageal squamous cell carcinoma. The results suggest that the impact on survival 176).…”
Section: Discussionmentioning
confidence: 97%
“…Hence, inhibiting pro-inflammatory mediators [ 26 , 27 ] and regulating immune reactions [ 25 ] are important considerations in the therapy of SAP. It has been confirmed that ulinastatin prevents the inflammatory response induced by SAP [ 28 ], and evidence also indicates that ulinastatin can regulate the immunological function through these special immune cells [ 18 , 29 ]. In the present study, we demonstrated that in SAP rat model, pro-inflammatory cytokines TNF-α and IL-1β and anti-inflammatory cytokine IL-10 all were increased significantly, while TGF-β was decreased.…”
Section: Discussionmentioning
confidence: 99%